Esophageal adenocarcinoma stage III: Survival based on pathological response to neoadjuvant treatment. (December 2017) - Schwameis, Katrin; Zehetner, Joerg; Hagen, Jeffrey A.; Oh, Daniel S.; Worrell, Stephanie G.; Rona, Kais; Cheng, Nathan; Samaan, Jamil; Green, Kyle M.; Lipham, John C.
Abstract: Background: Neoadjuvant chemoradiotherapy is the standard treatment for locally advanced esophageal adenocarcinomas (EAC). Pathological response is thought to be a major prognostic factor. Aims of this study were to determine the frequency of complete response and to compare the survival of complete and incomplete responders in stage III EAC. Methods: A retrospective review was performed of all stage III patients that underwent neoadjuvant therapy followed by esophagectomy between 1999 and 2015. Patients were classified into complete (pCR) versus incomplete responders (pIR). Results: 110 patients were included. Neoadjuvant chemotherapy was applied in 25 (23%) and chemoradiotherapy in 85 (77%) patients. Pathologic response was complete in 25% (n = 27) and was more common after chemoradiotherapy. Mean F/U interval was 36 months (0.3–173). There was a significant difference in the overall survival between complete and incomplete responders ( p = 0.036). Median survival in the pIR group was 24.4 months and the median survival was not reached during the observation time in pCR. The 3-year-survival-rate was 70% in pCR and 40% in pIR ( p = 0.01). Positive lymph nodes (ypN+) were present in 56 patients (51%). The 3-year-survival-rate was 59% in pIR with ypN0 and 29% in pIR with ypN+ ( p = 0.005). Conclusions: Complete response to neoadjuvant therapy has a significantly better overall and 3-year-survival after esophagectomy than incomplete response. In incomplete responders, residual lymph node disease was associated with a significantly worse survival. These findings suggest that the degree of pathologic response and lymph node status are major prognostic factors for survival in EAC patients with stage III disease.